2015
DOI: 10.1007/s11883-015-0517-6
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Bypass for Carotid Occlusion

Abstract: The 2-year risk of ipsilateral ischemic stroke following internal carotid artery occlusion (ICAO) in a patient undergoing maximal medical therapy is 5-8% per year. While medical therapy may reduce the risk of stroke, it does not completely eliminate it. Since the 1985 extracranial-intracranial (EC-IC) bypass study, additional trials have been conducted to further investigate the usefulness of EC-IC bypass surgery in more selected patients with cerebral ischemia and impaired hemodynamic reserve. These important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In the past 20 years, there has been considerable progress in imaging techniques, which has enabled physicians to identify conditions including hemodynamic ischemia and poor collateral circulation as well as patients at high risk of recurrent stroke ( 52 ).…”
Section: Imagingmentioning
confidence: 99%
“…In the past 20 years, there has been considerable progress in imaging techniques, which has enabled physicians to identify conditions including hemodynamic ischemia and poor collateral circulation as well as patients at high risk of recurrent stroke ( 52 ).…”
Section: Imagingmentioning
confidence: 99%
“…After this, investigators tried to find the subgroup of patients who might benefit from bypass surgery by determining hemodynamic consequences of ICA stenosis especially in elderly patients with atherosclerotic ICA stenosis. Recently, another trial about the effect of atherosclerotic carotid artery stenosis surgery (COSS) for stroke prevention again concluded that EC-IC bypass surgery did not reduce stroke compared with medical therapy [2][3][4][5]. Intracranial atherosclerosis was separately examined with similar results [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In extracranial [1][2][3][4][5] or intracranial [6,7,33] atherosclerotic ICA stenosis and in child and adult MMD [16][17][18][19][20][21][22][23][24][25][26]34], respectively with different reasons, basal/acetazolamide SPECT was proposed to evaluate the hemodynamic significance of already-characterized steno-occlusive lesions in ICA or cerebral arteries [6,7,21,22]. For elderly atherosclerotic patients, once functional impairment due to stenosis on the ipsilateral hemisphere is suspected, basal/acetazolamide SPECT was supposed to disclose the cases that need EC-IC bypass surgery [1,4,35], endarterectomy [36], stenting [37], or medical treatments. There is obviously a gray area of finding the indicated patients with failure of medical treatment, which depends on patients' suffering of a certain period taking the risk of strokes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations